Foreign Policy and National Interest - Gautam, Shreedhar (The Harvest, 2024)
Nepal’s foreign policy is guided by the collective desire of the people to preserve national independence and promote socio-economic interest. Our foreign policy is almost affected by geographical and cultural relations with the neighboring countriesIndia and China. Nepal must maintain very well-balanced relations with them in order to be a prosperous nation, and should not forget the Divya Upadesh of Prithivi Narayan Shah, late Kings Mahendra and Birendra (zone of peace). However, the post 1990 democratic Nepal is found lacking on many fronts in its foreign policy. Nepal should try to be self-reliant for basic needs of the people, based on common interest and mutual respect. Our political leadership must focus on economic development of the nation with a common voice and effort. But Nepal is being always a loser with India in various treaties. The issue of Kalapani, Lipulekha, Limpiyadhura is being a matter of dispute with India. Similarly, MCC, SPP, BRI are also disempowering us. Therefore, we have to maintain good relations with all by identifying our areas of mutual co-operation and collaboration keeping in mind our Panchasheela principles. Always we have to believe in people’s power and eliminate fear of foreign interference so as to make Nepal self-reliant and economically prosperous and peaceful.